Clinical perspective of myths about oral health in patients visiting tertiary hospital in eastern Nepal: A descriptive cross-sectional study - Yadav, Ajit; Giri, Dhirendra Kumar; Subedi, Krishna (Journal of Kathmandu Medical College, 2021)
Background: Nepalese population consists of people from different cultural backgrounds having strong influence of the various myths on health seeking behaviour. Myths are defined as stories shared by a group of people which are a part of their cultural identity. They have a strong influence in the life of individuals and their way of living including seeking treatment during illness. Objectives: The objective of this study was to assess the prevalence of myths related to oral health. Methods: A descriptive cross-sectional study was conducted in Nobel Medical College and Teaching hospital after obtaining ethical clearance from January 2021 to March 2021 using convenience sampling technique. Patients above 15 years visiting dental OPD were included and refused to participate were excluded. SPSS Statistics for Windows, version 21.0 was used for statistical analysis. Results: There were total 250 participants: 103 (41.2%) male and 147 (58.8%) female with mean age 34.43 ± 10.75 years and ranging from 18 to 62 years. Among the participants, 178 (72.1%) regarded fomentation of swelling with hot water while 72 (21.9%) were against it. Among all the participants 36 (14.4%) supported that there was presence of worm in decayed tooth whereas 214 (85.6%) were against it. Conclusion: The prevalence of myths about dentistry was high among study population which could be associated with poor early health seeking behaviour and poor compliance with treatment.